2022
DOI: 10.1108/ics-03-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Understanding employees’ information security–related stress and policy compliance intention: the roles of information security fatigue and psychological capital

Abstract: Purpose This study aims to explore the emotion-based mediator of information security fatigue in the relationship between employees’ information security–related stress (SRS) and information security policy (ISP) compliance intention and the effects of psychological capital (PsyCap) on relieving SRS and promoting compliance. Design/methodology/approach The authors tested a series of hypotheses by applying partial least squares–based structural equation modeling to survey data from 488 employees in Chinese en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Our study differs from the extant literature in proposing ISSR as a dynamic capability, which provides a basis to focus on the role of human factors in enabling and hampering an organization’s security posture. Factors such as IS fatigue and psychological capital (Chen et al ., 2022) have only recently emerged in related literature and, as far as we are aware, have not been explicitly considered as important in an organization’s ability to the resilient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study differs from the extant literature in proposing ISSR as a dynamic capability, which provides a basis to focus on the role of human factors in enabling and hampering an organization’s security posture. Factors such as IS fatigue and psychological capital (Chen et al ., 2022) have only recently emerged in related literature and, as far as we are aware, have not been explicitly considered as important in an organization’s ability to the resilient.…”
Section: Discussionmentioning
confidence: 99%
“…, 2021; Tu et al ., 2021). A few studies discuss the role of employees within organizations (Chen et al ., 2022; Jansen van Rensburg, 2021), firm characteristics (Tayaksi et al. , 2022), technology infrastructure of the firm, industry network features and characteristics of the security threat (Donalds and Osei-Bryson, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Table A1 shows that there are only a few studies that have investigated psychological capital in the information security context. Out of five studies, only two have identified a negative relationship between psychological capital and ISP compliance intention (Chen et al , 2022) and protection-motivated behaviors (Burns et al , 2017). In addition, no study has investigated factors that can improve psychological capital.…”
mentioning
confidence: 99%